Effectiveness of health education on knowledge of hypertension and diabetes among Indonesian migrant workers in Hong Kong - Arifah, Siti; Pribadi, Dimas Ria Angga (Universitas Muhammadiyah Magelang, 2025)
Hypertension and diabetes mellitus (DM) are non-communicable diseases with a high prevalence among Indonesian Migrant Workers (IMWs). Low health literacy and limited access to health services make IMWs vulnerable to complications. This community engagement activity aimed to enhance IMWs’ knowledge and skills in the prevention and management of hypertension and diabetes mellitus through community-based education and training. The methods employed included socialization, counseling, workshops, simple health check-ups, and mentoring. The program partnered with an IMW community under the guidance of the Consulate General of the Republic of Indonesia (KJRI) in Hong Kong, with 60 participants. The evaluation results show a significant increase, with knowledge in the good category for hypertension rising from 21.7% to 50.0%, and for diabetes mellitus from 21.7% to 55.0%. This program is effective in empowering IMWs through a transcultural and community-based approach.